Analysis Of ESD-Based Critical Thinking Attitude Assessment Rubric In Elementary Schools - Siti Nadia Herdianti; Ernawulan Syaodih; Ahmad Wahid Fudhaily (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
ESD (Educational for Sustainable Development) is one of UNESCO’s priority programs as an alternative in the education field and it is expected to direct students to realize a sustainable life as well as develop students’ critical thinking in their following life. Critical thinking is one of the eight key ESD competencies. The research objective was to determine the application of attitude assessment used by educators in elementary schools. This research was qualitative research with a descriptive approach. The subjects of this research were 6 elementary school classroom teachers in one of the schools in Pangandaran Regency. Data collection techniques used interview techniques and documentation studies on the attitude assessment rubric used by the teacher. The results indicated that there were 3 domains of ESD (Educational for Sustainable Development) that were related to the applicable curriculum (2013). The analysis results showed that there were 50% of the rubrics covering social, economic, and environmental. However, only 25% of the assessment rubrics used critical thinking indicators to assess students’ attitudes. Furthermore, the development of an instrument for assessing critical thinking based on ESD (Educational for Sustainable Development) was required